Peningkatan Hasil Belajar Siswa pada Muatan Pelajaran Matematika Kelas 4 melalui Metode Pembelajaran Tutor Sebaya di MIN I Yogyakarta - Sumarsih (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2019)
This study aims to describe the effectiveness of mathematics learning and describe the learning outcomes of mathematics with the Peer Tutor Learning method. This study uses the Classroom Action Research method, with data collection methods of documentation, observation and tests. The findings of this study that Learning Methods peer tutors are proven to increase the activity and effectiveness of learning and student learning outcomes. With this method, students who achieve grades above KKM have 18 students with a percentage of 62.07%, while students who achieve grades below the KKM have 11 students with a percentage of 37.93%. This increase in learning outcomes is also seen in the average score achieved, that is equal to 82,241 a value that exceeds the KKM, while the average value achieved previously is 74.69 a value that is still below the KKM. The limitations of this study were only carried out at MIN I Yogyakarta, class 4A with a total of 29 students.